Climate change adaptation through the water-energy-food nexus in southern Africa - Mpandeli, S.; Naidoo, D.; Mabhaudhi, Tafadzwanashe; Nhemachena, Charles; Nhamo, Luxon; Liphadzi, S.; Hlahla, S.; Modi, Albert Thembinkosi (MDPI, 2018)
Climate change is a complex and cross-cutting problem that needs an integrated and transformative systems approach to respond to the challenge. Current sectoral approaches to climate change adaptation initiatives often create imbalances and retard sustainable development. Regional and international literature on climate change adaptation opportunities and challenges applicable to southern Africa from a water-energy-food (WEF) nexus perspective was reviewed. Specifically, this review highlights climate change impacts on water, energy, and food resources in southern Africa, while exploring mitigation and adaptation opportunities. The review further recommends strategies to develop cross-sectoral sustainable measures aimed at building resilient communities. Regional WEF nexus related institutions and legal frameworks were also reviewed to relate the WEF nexus to policy. Southern Africa is witnessing an increased frequency and intensity in climate change-associated extreme weather events, causing water, food, and energy insecurity. A projected reduction of 20% in annual rainfall by 2080 in southern Africa will only increase the regional socio-economic challenges. This is exacerbating regional resource scarcities and vulnerabilities. It will also have direct and indirect impacts on nutrition, human well-being, and health. Reduced agricultural production, lack of access to clean water, sanitation, and clean, sustainable energy are the major areas of concern. The region is already experiencing an upsurge of vector borne diseases (malaria and dengue fever), and water and food-borne diseases (cholera and diarrhoea). What is clear is that climate change impacts are cross-sectoral and multidimensional, and therefore require cross-sectoral mitigation and adaptation approaches. In this regard, a wellcoordinated and integrated WEF nexus approach offers opportunities to build resilient systems, harmonise interventions, and mitigate trade-offs and hence improve sustainability. This would be achieved through greater resource mobilisation and coordination, policy convergence across sectors, and targeting nexus points in the landscape. The WEF nexus approach has potential to increase the resilience of marginalised communities in southern Africa by contributing towards attaining the Sustainable Development Goals (SDGs 1, 2, 3, 6, 7, and 13).